Assessment of diversity of Indian aromatic rice germplasm collections for morphological, agronomical, quality traits and molecular characters to identify a core set for crop improvement - G. S. V. Prasad; G. Padmavathi; K. Suneetha; M. S. Madhav; K. Muralidharan (CABI Agriculture and Bioscience)
Abstract Background Besides the Basmati, the aromatic rice germplasm (ARG) accessions are treasured for quality, medicinal value and aroma. The demand for aromatic rice is ever increasing. Genetic diversity is the source of variability to identify superior alleles controlling morphological, agronomic and quality traits, and molecular attributes. This study reports on the characterization of traits in ARG to identify a core set for breeding high-yielding varieties. Methods The genetic diversity was measured on the distinctness, uniformity and stability (DUS) of 46 traits in 208 Indian ARG in field, greenhouse and laboratory tests. We performed individual and combined analysis of DUS traits and molecular data generated using 55 SSR markers. The genetic distances between genotypes were estimated using Mahalanobis D2 analysis and clustering by standardized Euclidean2 distances, Ward Minimum variance, Gowers’ similarity index and PowerMarker. The aim was to derive a core set of non-Basmati ARG using PowerCore to deploy in crop improvement. Results Eighty-two alleles were detected. Alleles per marker ranged from 2 (RM505) to 5 (RM276) with an average of 3.04 alleles. The markers are informative in analyzing the diversity as the PIC values estimated varied from 0.17 (RM577 on chromosome 1) to 0.72 (RM276 on chromosome 6) with an average of 0.54 per locus. RM276 with repeat motif of (AG)8A3(GA) 33 on chromosome 6 was the most informative (amplified 5 alleles). The combined analysis had shown genotypes in a few clusters to be more diverse than others. SSR markers RM289, RM505, RM577 and RM22866 were identified as genotype specific markers. With PowerCore, 46 genotypes (22%) were identified as a core set of ARG that represent all the alleles detected in the entire set investigated. 2-Acetyl-1-pyrroline is considered to impart aroma; it was not detected by GC–MS tests in many ARG. Conclusions Forty-six genotypes in the core set have different maturity periods, plant statures, grain types and grain quality traits. A parent can be selected from the core set to improve aromatic rice depending on the breeding objective. The olfactory sensing of strong aroma emitted by cooked kernels of all ARG was found more decisive than the costly GC–MS tests.